“Reduced to a Whirlpool”: War, Sigmund Freud and Virginia Woolf’s (Late) Non-fiction - Paolo BUGLIANI (E-REA)
When the Second World War broke out, Virginia Woolf was absorbed in the final revision of Roger Fry, the final salute to her beloved friend whose biography she had been asked to write. If this writing experience is surely to be regarded as central to her experience of that limited portion of the conflict she endured, her readings too are to be considered as equally fundamental to the understanding of her participation in the conflict. To this effect this essay addresses Woolf’s first documented and systematic approach to Freud’s psychoanalytic theories, after the initial resistance she was careful to enact in the late 1920s.